Taxonomic studies of pteridophytes of Ambon and Seram (Moluccas) collected on Indonesian-Japanese botanical expeditions 1983–1986. XIII. Hymenophyllaceae - Iwatsuki, Kunio (PhytoKeys, 2019)
Abstract. Identifications are given for 713 specimens of Hymenophyllaceae collected on Ambon and Seram islands, the Moluccas, Indonesia, during 1983–86. The collection is composed of forty-seven species and one variety belonging to seven genera. The dataset is deposited in GBIF and available at https://www.gbif.jp/ipt/resource?r=seram_hymen.